Research on the establishment of evaluation index system of the aging construction of the community - Li, Kun; Mei, Wen-Bing; Huang, Yi-Zhe (Frontiers in Public Health, 2023)
Constructing the index system of community age-appropriate construction under the community home-based pension model, can provide a decision-making basis for the overall investment and priority satisfaction strategy of the community age-appropriate construction. Through questionnaire survey and statistical analysis, this paper evaluates and analyzes the satisfaction level of various indicators of community age-appropriate construction. The results show that the community's humanistic care, public environment, and socio-economic criteria have a significant linear relationship with the overall construction satisfaction level. There are significant differences in the overall satisfaction level of the elderly in the variables of "age, educational background, residence duration, residence personnel, number of children, and marital status". To this end, the article concludes with specific recommendations that improving elderly care services for the elderly with low age and high education, helping the elderly in the community to familiarize themselves with the community environment as soon as possible, cultivating the professional abilities of community service personnel, reflecting the warmth of the community for elderly care and improving social security capabilities are the core content of the future community building for aging.